Godzilla x Kong : the new empire [videorecording (Blu-Ray)] - Wingard, Adam, 1982-; Rossio, Terry; Barrett, Simon; Slater, Jeremy; Hall, Rebecca, 1982-; Henry, Brian Tyree; Stevens, Dan, 1982-; Hottle, Kaylee; Ferns, Alex, 1968-; Chen, Fala (Warner Bros. Entertainment Inc., 2024)
Relegated to Hollow Earth, Kong feels lonely and continues to search for his family, but instead finds a fearsome enemy imprisoned and on the verge of breaking out to conquer the humans. Alongside his human family -- Jia, Ilene, Trapper, and Bernie -- he ventures above ground to recruit help from Godzilla and other Titans, but making allies from old enemies is never easy!